Characterization of magnetorheological elastomer (MRE) engine mounts - Ladipo, Ismail; Darsivan, Fadly Jashi; Faris, Waleed Fekry (Elsevier, 2016)
This study presents simulation of Magnetorheological Elastomers (MREs) as engine mounts. A 4- parameter model is used to model the MRE mounts and the performance compared with passive or rubber mounts. Using relative displacements and force transmissibility at low frequencies and high frequencies respectively, the comparison show a 50% vibration reduction at resonance and varying degree of isolation at other broadband frequencies. Also by tuning the magnetic flux input, the MRE engine mounts can be used to further isolate vibration. These results suggest that the use of MRE as engine mounts deserves more attention.